Exploring The Implementation Challenges of Inclusive Education Policies in Primary Classroom Practices - Totini, Anjum Tasnim; Fuad, A Z M; Alam, Md Nurkutubul (South Asian Journal of Social Sciences and Humanities, 2025)
This study delves into the implementation challenges of inclusive education policies,  highlighting the major factors of not assuring inclusiveness and quality in the Bangladeshi  primary classroom context. This study engaged in exploring the gaps and why the  implementation of the policies has not been considered properly. Data for this study was  collected from four primary schools using semi-structured interviews of a head teacher and a  teacher from each of four schools, classroom observation (approximate 40-45 students in a  classroom), and thematic analysis was employed to analyze the data sets. The findings reveal  gaps in teachers, administrators, and students’ awareness as they have limited knowledge of  inclusive education principles and limited stakeholder engagement. Classroom observation  also reveals insufficient inclusive-practice in classrooms to accommodate children with special  needs, with inadequate teacher training and lack of cooperation from stakeholders which affect  communication engagement for special needs children. This study implies that the authorities  should create some specific opportunities both for the teachers and students to implement  inclusiveness and its practice in the classroom.
Keywords: Bangladeshi primary schools; classroom practice; implementation challenges; inclusive education; policy Implementation